2006
DOI: 10.1051/0004-6361:200600011
|View full text |Cite
|
Sign up to set email alerts
|

Galactic dynamo and helicity losses through fountain flow

Abstract: Nonlinear behaviour of galactic dynamos is studied, allowing for magnetic helicity removal by the galactic fountain flow. A suitable advection speed is estimated, and a one-dimensional mean-field dynamo model with dynamic alpha-effect is explored. It is shown that the galactic fountain flow is efficient in removing magnetic helicity from galactic discs. This alleviates the constraint on the galactic mean-field dynamo resulting from magnetic helicity conservation and thereby allows the mean magnetic field to sa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
193
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 145 publications
(206 citation statements)
references
References 30 publications
13
193
0
Order By: Relevance
“…However, there has been no such hint from Hα observations of edge-on spiral galaxies so far (Hoopes et al 1999). Alternatively, the magnetic pitch angle may be affected by gas flows, for instance, by outflows that become weaker towards the outer disk and can decrease the effective dynamo number (Shukurov et al 2006;Sur et al 2007). …”
Section: Pitch Angles Of the Spiral Magnetic Field And The Spiral Strmentioning
confidence: 99%
“…However, there has been no such hint from Hα observations of edge-on spiral galaxies so far (Hoopes et al 1999). Alternatively, the magnetic pitch angle may be affected by gas flows, for instance, by outflows that become weaker towards the outer disk and can decrease the effective dynamo number (Shukurov et al 2006;Sur et al 2007). …”
Section: Pitch Angles Of the Spiral Magnetic Field And The Spiral Strmentioning
confidence: 99%
“…3 Dynamo models with helicity fluxes Shukurov et al (2006) small scale helicity from the disc region. They showed that in a simple local galactic dynamo model, the field can grow to saturation levels in a turbulent diffusion time, i.e.…”
Section: Magnetic Helicity Conservationmentioning
confidence: 99%
“…Nevertheless this constraint may be lifted if the system is able to rid itself of small-scale helicity through at least one of several ways such as open boundaries, advective, diffusive and shear-driven fluxes (Shukurov et al 2006;Zhang et al 2006;Sur et al 2007;Käpylä et al 2008;Brandenburg et al 2009;Guerrero et al 2010). Even though the helicity constraint in direct numerical simulations (DNS) of dynamos with strong shear have been clearly identified, the results can be matched with mean field models with a weaker algebraic quenching than α 2 dynamos .…”
Section: Introductionmentioning
confidence: 99%